2003
DOI: 10.1046/j.1440-1630.2003.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

A psychospiritual integration frame of reference for occupational therapy. Part 1: Conceptual foundations

Abstract: This paper introduces a new clinical practice framework -the psychospiritual integration frame of reference.It opens with a broad discussion on spirituality as articulated within occupational therapy and occupational science literature, followed by a brief introduction into framework's paradigm and interdisciplinary knowledge base. A general description of the frame of reference's major constructs and principles, as well as theoretical arguments concerning order, disorder, and the model's dynamics, are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 26 publications
1
84
0
Order By: Relevance
“…Similarly, the students are expected to apply the strategies of community entry, needs assessment and needs analysis so that they might address the community's needs 22,[30][31][32][33][34] . In addition, the students and community members employ the Assets Based Community Development (ABCD) strategy to map the assets around the community so that these resources may be identified and located, together with relevant organisations, with the aim of formulating networks within the communities 35,36 . Several studies have revealed that both community fieldwork education and practice seemed to omit spirituality [37][38] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the students are expected to apply the strategies of community entry, needs assessment and needs analysis so that they might address the community's needs 22,[30][31][32][33][34] . In addition, the students and community members employ the Assets Based Community Development (ABCD) strategy to map the assets around the community so that these resources may be identified and located, together with relevant organisations, with the aim of formulating networks within the communities 35,36 . Several studies have revealed that both community fieldwork education and practice seemed to omit spirituality [37][38] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have revealed that both community fieldwork education and practice seemed to omit spirituality [37][38] . Regarding community fieldwork practice, the occupational therapy students learn to apply their knowledge and understanding of the community fieldwork process by engaging individuals and communities in planning and implementation of the community projects 27,[32][33][34][35] . Therefore, Kang 36:96 refers to the community projects as 'sociospiritual experiments' because they seem to be community-driven and aim to reclaim local culture, local economy and local ecology in a spirit of ethical living, inclusiveness and spiritual well-being for all.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations